Desenvolvimento de mudas de maracujazeiro amarelo e tubetes - Silva, Ana Paula Pereira da (2006)
A major part of the success of a crop is related to the use of seedlings of good quality. Little information is found in agricultural literature regarding certain details in the production of yellow passion fruit seedlings in tubettes, which makes the activity for seedling producers quite difficult. The present research had, as a general objective, to extend the knowledge of the production of yellow passion fruit in tubettes as well as to study different techniques for sowing, dormancy break, types of cuttings, utilization of rooting hormones, besides volume and substrate granulometry with the purpose of obtaining seedlings of good quality in the environmental conditions of Uberlândia, M.G. In the first chapter information regarding the importance of the crop is presented, and some procedures are adopted in the subsequence chapters. In the second chapter the aim was to evaluate the influence of the volume and granulometry of a commercial substrate on the vegetative seedling growth development. It was conclude that the reduction of the volume and substrate granulometry affected the aeration and the drainage, so reducing growth and development of yellow passion fruit seedlings. The seedlings produced in the commercial substrate with the original granulometry and in the volume of 180 mL attained best responses for the following traits: plant height, number of leaves, stem diameter and root and shoots dry matter. In the third chapter, the objective was to evaluate the capacity of rooting and development of the seedlings proceeding from cuttings at the apical, median and basal branches of the yellow passion fruit submitted to different environmental conditions in Uberlândia, M.G. The results obtained showed that the cuttings originated from the median and basal shoots of the yellow passion fruit presented higher percentage of rooting (79,1% and 91,6% respectively), even with no application of IBA ( Indolebutyric acid ). On the other hand, the use of the auxin improved the apical cutting rooting, reaching 80,5% of cuttings rootings with the dose of 500 mg L-1, besides that, the hormone promoted also an increase in the sprout lengths and in the amount of root and shoot dry matter. In chapter four the aim was to evaluate the influence of sowing depth and the break of dormancy on the vigor and vegetative development of the seedlings. The resulted obtained showed that the yellow passion fruit seedlings, regardless of being or not submitted to techniques for dormancy breakage, presented higher germination in a 2,0 cm sowing depth. Seeds that were immersed in water at room temperature for 24 hours and sown at a depth of 2,0 cm presented seedling emergence in a shorter period of time. The techniques of immersion in water at room temperature for 24 hours and immersion in water for 15 minutes at the temperature of 35 º C for 15 minutes were quite efficient and promoted high seed germination ( 96,9% and 95,4% ) respectively, as well as development of seeds with greater number of leaves, plant height and greater quantity of roots dry matter.